The interrogative modality in Spanish and Chinese: a functionalist focus - Shang 尚培珠, Peizhu; Elvira-García, Wendy; Roseano, Paolo (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This article presents a contrastive analysis of the interrogative modality in Spanish and Chinese, based on a functional-pragmatic theoretical framework. After research, firstly we have shown that the interrogative modality can not only perform the prototypical function of requesting information, but also serves for diverse communicative purposes, such as confirming hypotheses, formulating requests or orders, offering objects or suggestions, expressing surprises, etc. These pragmatic functions are encoded through different discursive and grammatical strategies, which are characterized by distinct combinations of morphological, syntactic and prosodic resources. Additionally, by comparing the two languages in this study, we demonstrated that the greatest difference between them in terms of the interrogative modality derives from the suprasegmental levels, modal particles and word orders
Keywords: Interrogative modality; pragmatic function; linguistic strategy; comparison between Spanish and Chinese